2016
DOI: 10.1080/21655979.2016.1227141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testosterone on the proliferation and collagen synthesis of cardiac fibroblasts induced by angiotensin II in neonatal rat

Abstract: The objective is to explore the effect of testosterone on the proliferation and collagen synthesis of neonatal rat cardiac fibroblasts (CF) induced by Angiotensin II (Ang II) and the underlying mechanisms. Derived from neonatal rats, the CFs were divided into 4 groups: the control group, Ang II group, testosterone group, and testosterone C Ang II group in vitro. Cell cycle distribution, collagen counts, and phosphorylated extracellular signal-regulated kinase (ERK1/2) (p -ERK1/2) expression were assessed by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The increases in the number of fibroblasts demonstrate the positive effects of electrical stimulation to factors involved in the collagen content . Therapies that stimulate the synthesis of type I collagen and lead to increased maturation of collagen are used in the treatment of injury's in bone repair models . The evaluation of collagen I and III has been an important indicator of the progress of repair where it can be observed that the synthesis of type III collagen is gradually replaced by that of type I collagen, an essential process during bone remodeling phase, indicating tissue maturation …”
Section: Discussionmentioning
confidence: 99%
“…The increases in the number of fibroblasts demonstrate the positive effects of electrical stimulation to factors involved in the collagen content . Therapies that stimulate the synthesis of type I collagen and lead to increased maturation of collagen are used in the treatment of injury's in bone repair models . The evaluation of collagen I and III has been an important indicator of the progress of repair where it can be observed that the synthesis of type III collagen is gradually replaced by that of type I collagen, an essential process during bone remodeling phase, indicating tissue maturation …”
Section: Discussionmentioning
confidence: 99%
“…TGF- β 1 represents one of the most important cytokines in this regard, as it appears to promote vascular proliferation, migration, and increasing collagen and elastin during adventitia remodeling [ 5 , 23 ]. Other factors include the expressions of MMPs and NF- κ B, all of which contribute to regulating vascular proliferation and migration responses [ 24 ]. MMP-1 is an extracellular matrix protein hydrolysis enzyme, which participates in regulating vascular remodeling and cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a direct impact of testosterone promoting enhanced collagen synthesis has also been observed in dermal fibroblasts (Yoo et al, ). Finally, testosterone induces increases in the production of angiotensin, thereby leading to enhanced neonatal cardiac fibroblast proliferation and subsequent collagen production (Yang et al, ). Thus, the fibrosis observed upon high‐dose testosterone supplementation may either be the direct result of testosterone itself, or a secondary compensatory effect.…”
Section: Introductionmentioning
confidence: 99%